Legitimacy, civil society, and state crime - Ward, Tony (Social justice, 2000)
Part of a special issue on neoliberalism, militarism, and armed conflict. The writers integrate the concepts of legitimacy, hegemony, and civil society, which emanate from the disciplines of political science and international relations, into a criminological framework in order to understand state crime. They clarify the relationship of these concepts to deviance and human rights and outline how they contribute to explanations of state crime and its control.